(untitled) (Revista Argentina de Cirugía, 2021)
Parathyroid carcinoma is a rare endocrine malignancy, accounting for less than 1% of cases of primary hyperparathyroidism. We report the case of a female patient hospitalized for acute kidney failure associated with hypercalcemia, parathyroid hormone levels 8 times above the normal value, and a nodular mass behind the thyroid gland on magnetic resonance imaging. The patient underwent en bloc resection of the parathyroid glands and the right thyroid lobe.